Biological and prognostic implications of biopsy upgrading for high‐grade upper tract urothelial carcinoma at nephroureterectomy. (9th November 2022) - Katayama, Satoshi; Pradere, Benjamin; Grossman, Nico C.; Potretzke, Aaron M.; Boorjian, Stephen A.; Ghoreifi, Alireza; Daneshmand, Sia; Djaladat, Hooman; Sfakianos, John P.; Mari, Andrea; Khene, Zine‐Eddine; D'Andrea, David; et al.
Abstract : Objectives: Technical limitations of ureteroscopic (URS) biopsy has been considered responsible for substantial upgrading rate in upper tract urothelial carcinoma (UTUC). However, the impact of tumor specific factors for upgrading remain uninvestigated. Methods: Patients who underwent URS biopsy were included between 2005 and 2020 at 13 institutions. We assessed the prognostic impact of upgrading (low‐grade on URS biopsy) versus same grade (high‐grade on URS biopsy) for high‐grade UTUC tumors on radical nephroureterectomy (RNU) specimens. Results: This study included 371 patients, of whom 112 (30%) and 259 (70%) were biopsy‐based low‐ and high‐grade tumors, respectively. Median follow‐up was 27.3 months. Patients with high‐grade biopsy were more likely to harbor unfavorable pathologic features, such as lymphovascular invasion ( p  < 0.001) and positive lymph nodes (LNs; p  < 0.001). On multivariable analyses adjusting for the established risk factors, high‐grade biopsy was significantly associated with worse overall (hazard ratio [HR] 1.74; 95% confidence interval [CI], 1.10–2.75; p  = 0.018), cancer‐specific (HR 1.94; 95% CI, 1.07–3.52; p  = 0.03), and recurrence‐free survival (HR 1.80; 95% CI, 1.13–2.87; p  = 0.013). In subgroup analyses of patients with pT2‐T4 and/or positive LN, its significant association retained. Furthermore, high‐grade biopsy in clinically non‐muscle invasive disease significantly predicted upstaging to final pathologically advanced disease (≥pT2) compared to low‐grade biopsy. Conclusions: High tumor grade on URS biopsy is associated with features of biologically and clinically aggressive UTUC tumors. URS low‐grade UTUC that becomes upgraded to high‐grade might carry a better prognosis than high‐grade UTUC on URS. Tumor specific factors are likely to be responsible for upgrading to high‐grade on RNU.